Sistem Informasi Penjualan Biota Laut Panarukan Shell Berbasis Web - Mustika Dewi Kurnia (Jurnal Ilmiah Informatika, 2019)
Panarukan-Shell is one of the warehouses in the panarukan that provides raw materials such as marine biota craft such as raw materials from ornamental shells. The Panarukan-Shell location is on Jl. Cokroaminoto Rt 01 Rw 02 Panarukan, Situbondo District. This warehouse provides various types of marine biota. The financial management associated with this information system is the process of purchasing, selling and expending by shell-sharers in order to facilitate the recording of financial statements to find out the details of reports from income, expenses, purchases, sales, inventory to profit and loss. The data must be completely accurate in accordance with the reality. Purchasing and sales data management in the shell-pan still uses manual recording system on the book so it has not been able to facilitate the owner in managing the calculation data or income income. Creating a new web-based information system is expected to help owners in terms of financial accountability of existing workflow. In this case makes it easier in adding, deleting, and changing data and search data purchase, sales, and expenditure.